A randomized controlled trial of bedtime music for insomnia disorder. (24th January 2019) - Jespersen, Kira Vibe; Otto, Marit; Kringelbach, Morten; Van Someren, Eus; Vuust, Peter
Summary: Music is often used as a self‐help tool to alleviate insomnia. To evaluate the effect of bedtime music listening as a strategy for improving insomnia, we conducted an assessor‐blinded randomized controlled trial. Fifty‐seven persons with insomnia disorder were included and randomized to music intervention ( n = 19), audiobook control ( n = 19) or a waitlist control group ( n = 19). The primary outcome measure was the Insomnia Severity Index. In addition, we used polysomnography and actigraphy to evaluate objective measures of sleep, and assessed sleep quality and quality of life. The results showed no clear effect of music on insomnia symptoms as the group × time interaction only approached significance (effect size = 0.71, p = .06), though there was a significant improvement in insomnia severity within the music group. With regard to the secondary outcomes, we found a significant effect of the music intervention on perceived sleep improvement and quality of life, but no changes in the objective measures of sleep. In conclusion, music listening at bedtime appears to have a positive impact on sleep perception and quality of life, but no clear effect on insomnia severity. Music is safe and easy to administer, but further research is needed to assess the effect of music on different insomnia subtypes, and as an adjunctive or preventive intervention.